The application of solar energy in water reuse - Prasad G. (My University, 2025)
The application of photocatalysed oxidation in water reuse technology is described. Results with a sequencing batch reactor showed that 4 hours contact of the raw sewage with 0·5 mg dye sorbed g−1 fly ash in sunlight, under experimental conditions, significantly reduced the organic and bacteriological load and rendered it fit for use in irrigation or for discharge. The effect of variables such as contact time or amount of dye sorbed on COD, MBAS and MPN counts were investigated and the results interpreted in terms of enhanced photoactivity and biodegradation in the sorbed state. The process appears to be well suited to commercial exploitation as it is safe, quick and economical. Copyright © 1987 Society of Chemical Industry